Septoplasty with or without concurrent turbinate surgery versus non-surgical management for nasal obstruction in adults with a deviated septum: a pragmatic, randomised controlled trial. Issue 10195 (27th July 2019) - van Egmond, Machteld M H T; Rovers, Maroeska M; Hannink, Gerjon; Hendriks, Carine T M; van Heerbeek, Niels
Summary: Background: Septoplasty (surgical correction of the deviated nasal septum) is the most frequently performed ear, nose, and throat operation in adults, but no randomised controlled trials or non-randomised comparative studies on the effectiveness of septoplasty have been published. Consequently, health-care providers, health insurance companies, and policy makers are concerned about the effectiveness of the procedure. We aimed to assess the effectiveness of septoplasty for nasal obstruction in adults with a deviated septum. Methods: We did this open, multicentre, pragmatic, randomised controlled trial in 16 secondary and two tertiary referral hospitals in the Netherlands. Adults (aged ≥18 years) with nasal obstruction, a deviated septum, and an indication to have septoplasty done were randomly allocated (1:1) to receive either septoplasty with or without concurrent turbinate surgery or non-surgical management. Patients were stratified by sex, age (<35 years or ≥35 years), and deviation severity (mild, moderate, or severe). The primary outcome was health-related quality of life, measured with the validated Glasgow Health Status Inventory at 12 months. Analyses were done on an intention-to-treat basis. The trial is registered with the Netherlands Trial Register, number NTR3868. Findings: Between Sept 2, 2013, and Dec 12, 2016, we randomly assigned 203 participants to receive either septoplasty with or without concurrent turbinate surgery (n=102) or non-surgical management (n=101). 189 participants were analysed at 12 months. At 12 months, mean score on the Glasgow Health Status Inventory of patients assigned to septoplasty was 72·2 (SD 12·2) and for those assigned to non-surgical management was 63·9 (SD 14·5, mean difference 8·3 [95% CI 4·5–12·1], favouring septoplasty). Septal abscess occurred in one surgical patient and septal perforation in two surgical patients. No side-effects of nasal medication were reported. Interpretation: Septoplasty is more effective than non-surgical management for nasal obstruction in adults with a deviated septum. This effect was sustained up to 24 months of follow-up. Funding: The Netherlands Organisation for Health Research and Development (ZonMw).